Library Application and Book Return Schedule Reminder using Short Message Service (SMS) at State Vocational School of Jenawi - Ixnu Subextyo; Ahmad Subhan Yazid; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2015)
The Library of the State Vocational School of Jenawi implements a manual database system where the transaction process is slow and inefficient. The frequent delay in returning books also adds to the problems. This study aims to build a library application that manages library data, including member data, borrowing-returning books data, calculating fines for returning books, and book searches. The method used is SDLC (System Development Life Cycle) which consists of the analysis, design, implementation and testing. The application built with Delphi can manage library data, handle book circulation, and automatically send Short Message Service (SMS) to the borrower as a reminder of the book's return schedule.